2017
DOI: 10.1016/j.cam.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

A latency fractional order model for HIV dynamics

Abstract: We study a fractional order model for HIV infection where latent T helper cells are included. We compute the reproduction number of the model and study the stability of the disease free equilibrium. We observe that the reproduction number varies with the order of the fractional derivative α. In terms of epidemics, this suggests that varying α induces a change in the patients' epidemic status. Moreover, we simulate the variation of relevant parameters, such as the fraction of uninfected CD4 + T cells that becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 37 publications
0
50
0
2
Order By: Relevance
“…In addition, our exact solutions in (54), (66), (105), and (107) are equivalent to that, which were constructed by the exp(−Φ( )) method, in [66] in which they were expressed in (28), (29), (30), and (32), respectively. Furthermore, our exact solutions in (79) and (106) have the same mathematical structure as solution (29) in [67] using the exp-function method. Hence, the novel ( / )-expansion method used in our work have provided more new forms of the exact solutions of (28) since the method gives more free parameters than the existing methods utilized previously.…”
Section: The Exact Solutions Of (28) Obtained Using the Unknown Constmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our exact solutions in (54), (66), (105), and (107) are equivalent to that, which were constructed by the exp(−Φ( )) method, in [66] in which they were expressed in (28), (29), (30), and (32), respectively. Furthermore, our exact solutions in (79) and (106) have the same mathematical structure as solution (29) in [67] using the exp-function method. Hence, the novel ( / )-expansion method used in our work have provided more new forms of the exact solutions of (28) since the method gives more free parameters than the existing methods utilized previously.…”
Section: The Exact Solutions Of (28) Obtained Using the Unknown Constmentioning
confidence: 99%
“…Since fractional derivatives [25] such as the RiemannLiouville derivative and the Caputo derivative can describe the memory and hereditary properties of materials and processes which is different from ordinary derivatives, fractional differential equations (FDEs), which are associated with 2 Mathematical Problems in Engineering fractional derivatives and the generalization of the classical differential equations of integer orders, are expansively used to model various complex phenomena in many study fields such as physics [26], engineering [27], finance [28], and biology [29]. It has been found that the above-mentioned methods with their improvements (see, e.g., [30][31][32][33]) are also widely applicable to solve FDEs.…”
Section: Introductionmentioning
confidence: 99%
“…In many applications, it has been shown that modeling the behavior of dynamical systems by fractional differential equations has more advantages than integer‐order modeling …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the integer order and the fractional order models together provide a better understanding of the dynamics of the coinfection. Also, these authors in a previous study considered a latency fractional order model for HIV dynamics where includes latent T helper cells. Jajarmi and Baleanu examined the pathological behavior of HIV‐infection using a new model based on three different operators of fractional derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…We apply the Grunwald-Letnikov method by using binomial coefficients [48,[56][57][58]. (Figures 14-16).…”
Section: (Iii) Grunwald-letnikov Algorithm (Binomial Coefficients)mentioning
confidence: 99%